De novo noncutaneous malignancies after kidney transplantation are associated with an increased risk of graft failure: results from a time‐dependent analysis on 672 patients. (1st August 2016) - Cena, Tiziana; Musetti, Claudio; Quaglia, Marco; Magnani, Corrado; Stratta, Piero; Bagnardi, Vincenzo; Cantaluppi, Vincenzo
Summary: The aim of this study was to evaluate the association between cancer occurrence and risk of graft failure in kidney transplant recipients. From November 1998 to November 2013, 672 adult patients received their first kidney transplant from a deceased donor and had a minimum follow‐up of 6 months. During a median follow‐up of 4.7 years (3523 patient‐years), 47 patients developed a nonmelanoma skin cancer (NMSC) and 40 a noncutaneous malignancy (NCM). A total of 59 graft failures were observed. The failure rate was 6 per 100 patient‐year (pt‐yr) after NCM versus 1.5 per 100 pt‐yr in patients without NCM. In a time‐dependent multivariable model, the occurrence of NCM appeared to be associated with failure (HR = 3.27; 95% CI = 1.44–7.44). The effect of NCM on the cause‐specific graft failure was different ( P = 0.002) when considering events due to chronic rejection (HR = 0.55) versus other causes (HR = 15.59). The reduction of the immunosuppression after NCM was not associated with a greater risk of graft failure. In conclusion, our data suggest that post‐transplant NCM may be a strong risk factor for graft failure, particularly for causes other than chronic rejection.